Pengaruh Persepsi Teknologi Informasi, Risiko dan Handling Complaint terhadap Minat Nasabah dalam Menggunakan Internet Banking di Bank BSI KC Suniaraja Bandung - Rissa Aulia; Adi Indradi Wazdi (Jurnal Dimamu, 2022)
Based on observations, that the background of this research is that there is a lack of customers who use internet banking. This is caused by several factors including differences in perceptions of information technology, risk and complaint handling.This study aims to determine how the effect of information technology perception, risk and complaint handling both on customer interest in using partial and simultaneous Internet Banking at BSI Syariah KC Suniaraja Bandung.The research object of this report is Perception of Information Technology Risk, and Handling Complaint to Customer Interest in using Internet Banking at BSI Suniaraja Bandung.The results of the study show that there is an influence between the Information Technology Perception variable on Customer Interest, which is 1.2% or t count of 2.290 > 1.989, There is an influence between the Risk variable on Customer Interest which is 2.3%. Or t count 11.870 > 0.256 with a significant value of 0.049 < 0.1. There is a significant influence on the Handling Complaint variable on customer interest, which is 35.1%, it can be seen from the t count of 13.310 > 0.256 with a significant value of 0.007 < 0, 1. Simultaneously there is a significant influence on the variable Perception of Information Technology, Risk to Customer Interest, which is 36.5%, this can be seen from the Fcount of 18.430 > 2.270 and a significant value of 0.000 < 0.1.